Studies on the biology and ecology of Amblyomma Herbraem Koch, 1844 and other tick species (Ixodidae) of the Eastern Cape - Norval, R A I (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1975)
Tick borne diseases of livestock are among the most important factors which have retarded economic development in many parts of Africa. Modification of the environment due to the expansion of agriculture into previously undeveloped areas, together with the introduction of livestock, has disturbed the natural balance which existed between ticks and indigenous hosts. Many tick species have adapted to domestic stock, and in some instances have spread over large areas which were previously uninfested. A number of tick species which are parasitic on domestic stock, eg. Amblyomma hebraeum Koch, 1844, Boophilus decoloratus (Koch, 1844), Rhipicephalus evertsi Neumann, 1897 and Rhipicephalus appendiculatus Netunann, 1901, are vectors of pathogenic micro-organisms. Unlike indigenous hosts however, domestic stock have no innate immunity to tickborne diseases. Intro., p. 1.
Keywords: Ticks -- South Africa -- Eastern Cape; Ixodidae -- South Africa -- Eastern Cape